Treatment of Open-Angle Glaucoma with iStent Implantation Combined with Phacoemulsification in Polish Caucasian Population - Kozera M (Dove Medical Press, 2021)
Milena Kozera,1 Joanna Konopińska,2 Zofia Mariak,2 Marek Rękas1 1Department of Ophthalmology, Military Institute of Medicine, Warsaw, Poland; 2Department of Ophthalmology, Medical University of Bialystok, Białystok, PolandCorrespondence: Joanna KonopińskaDepartment of Ophthalmology, Medical University of Białystok, M. Sklodowska-Curie 24A STR, Białystok, 15-276, PolandTel +48-857468372Fax +48-857468604Email joannakonopinska@o2.plPurpose: The aim of this investigation was to evaluate the impact of iStent (the first-generation trabecular bypass) implantation with phacoemulsification on the intraocular pressure (IOP) and glaucoma medication in subjects with mild to moderate open-angle glaucoma (OAG) and cataract in a Polish Caucasian population.Patients and Methods: This prospective case series covered 78 eyes of (57 Polish Caucasian patients) that had undergone iStent implantation in conjunction with cataract surgery. Patients were surveyed preoperatively and at postoperative day 1, week 1, and months 1, 3, 6, 12, and 24. Pre- and postoperative outcome measurements included visual acuity, IOP, and medication burden. Intraoperative and postoperative complications were noted for the safety profile. For effective treatment, an IOP reduction ≥ 20% was assumed, regardless of the use of IOP-lowering drops. Complete surgical success was defined as an IOP ≤ 15 mmHg, medications free, and a qualified surgical success as IOP ≤ 15 mmHg with or without medications.Results: Post-operatively at two years, mean IOP reduced from 18.5 mmHg to 16.1 mmHg. The mean medication burden dropped from 1.8 to 0.4 at the end of follow-up. Preoperatively, 2 (2.6%) eyes were medication free, but by postoperative month 24, 53 (68%) eyes were medication-free (p < 0.05). Effective treatment was achieved in 50 cases (64%) at the end of follow-up period. Kaplan–Meier cumulative incidence of qualified success was 51.9% after 24 months, CI95 [41.9%; 64.4%], while cumulative incidence of complete success after 2 years of observation was 35.1%, CI95 [25.9%; 47.5%].Conclusion: The iStent device combined with a cataract surgery served to decrease, significantly and positively, both IOP and medication use in the 24-months follow-up in patients with coexistent OAG and cataract in Polish patients.Keywords: iStent first generation, trabecular by-pass, medication burden, microinvasive glaucoma surgery, open-angle glaucoma